Performance evaluation of the perturb & observe and incremental conductance algorithms according to the EN 50530 dynamic efficiency test - Onur Kırcıoğlu; Murat Ünlü; Sabri Çamur (Sakarya Üniversitesi Fen Bilimleri Enstitüsü Dergisi)
The perturb & observe (P&O) andincremental conductance algorithms, which are widely used in maximum powerpoint tracker systems. In this study, A SEPIC (single-ended primary inductanceconverter) DC/DC converter is designed for maximum power point tracker, andboth algorithms are implemented on the SEPIC converter by using DSP. Theperformance of maximum power point tracker (MPPT) in PV system under dynamicenvironmental conditions (such as irradiation, dirt, temperature) is veryimportant in the point of its efficiency. EN 50530 standard, which is providesa procedure for the measurement of the efficiency, is used to evaluate thedynamic performance of the both MPPT algorithms in this paper. The experimentsare conducted using the dynamic performance test platform that consists of a PVarray simulator, SEPIC DC/DC converter and DSP. The results show thatefficiencies and performances of the both MPPT algorithms are very close toeach other. The obtained results show that both algorithms have fast dynamicresponse and the average efficiencies are over 99% with the designed system at100Hz of MPPT frequencies for over all slopes and irradiance in the range from0.5 to 100 W/m2/s and 100 W/m2- 1000W/m2 asdefined by EN 50530 standard.